ANALISIS GOOD CORPORATE GOVERNANCE DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI - Ayuningtyas, Brigitta Audrey; Kusumawati, Synthia Madya; Petronila, Thio Anastasi (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2022)
The purpose of this study is to analyze the effect of good corporate governance and capital structure on firm value with the mediating role of financial performance in consumer goods companies in the cyclicals sector listed on the Indonesia Stock Exchange in 2019-2021. This research is a quantitative research with a descriptive approach. The data used in this study is secondary data in the form of company financial statements obtained from the IDX data. The sample used in this study was 197 consumer goods companies in the cyclical sector listed on the IDX (Indonesian Stock Exchange) in 2019-2021. Data analysis techniques in this study using SPSS. The results in this study indicate that good corporate governance and capital structure affects firm value. Meanwhile, financial performance cannot mediate good corporate governance and capital structure on firm value